Legal Review Of The Fulfillment Of Wastewater Quality Standards In The Hotel Industry In Cirebon City - Efionita Sepfiani; Aria Wirakusuma; Rudi Kurniawan; Endang Sutrisno; Harmono Harmono (Al-Makki Publisher, 2024)
This study aims to control water pollution by conducting observations on the hotel industry in Cirebon City regarding the implementation of compliance with the standardization of wastewater quality standard parameters according to Ministerial Regulation No. P 68 of 2016. Research methods were conducted openly through interview techniques regarding monitoring and management of wastewater produced by the Hospitality Industry in Cirebon City. The results of the study identified that from the hotel industry in the city of Cirebon which is the object of research, the quality standard of wastewater produced exceeds the standardization of meeting quality standards so that there is still a risk of water pollution. The handling can be this problem by conducting strict monitoring by the environmental service and providing knowledge or information related to the management of wastewater quality standards properly so that the content of the waste produced does not endanger the flow of rivers and seas in the city of Cirebon. The approach that must be taken in order to understand and be able to maximize the treatment of liquid waste with a wastewater management plant (IPAL) is to consult the Environmental Service in order to get direction to cooperate with third parties (outsourcing). Observations also state that there is still one hotel that does not use IPAL and in the hotel's activities, the waste is purely dirty and pollutes the river flow in Cirebon City.